Board Diversity and Audit Quality among Selected Listed Food and Beverage Firms on the Nigeria Exchange Group - Segun Idowu Adeniyi; Vincent Ayeole Aderobaki (JASF: Journal of Accounting and Strategic Finance, 2022)
This study aims to determine the effect of ethnicity diversity, skill, expertise, and experience diversity and interaction of ethnicity diversity and skill, expertise, and experience diversity on the audit quality of listed food and beverage firms in Nigeria. The study used an Ex-Post Facto research design. Five beverage companies as of December 2019 were listed on the Nigerian Exchange Group and make up the study's population. A purposive sampling technique was adopted in selecting the three listed food and beverage firms that form the unit of analysis for this study. The panel data were derived from annual reports and accounts with the Nigeria Stock Exchange Factbook for the period of ten years spanning from 2010 to 2019. The Ordinary Least Square statistical technique was adopted in the analysis of data. The statistical procedures were programmed using SPSS 20.0 software. The study discovered that ethnicity diversity and skill, expertise, and experience diversity do not significantly affect audit quality while the interaction of ethnicity diversity and skill, expertise, and experience diversity affects audit quality. Therefore, the study recommends among others that ethnic diversity need not consider in corporate board composition and it should not be made compulsory for board members to have certificates. Related to accounting, have experience in financial reporting or auditing.